The Critical Thinking in Elementary Science: Effectiveness of Contextual Flipped Group Classroom (CFGC) - Nasrah, Nasrah (Mimbar Ilmu, 2025)
21st century learning consists of several essential competencies to be achieved, one of which is the ability to think critically. Various research findings on the need to increase students' critical thinking in science subjects. The purpose of this study was to determine the effect of the CFGC learning model on the critical thinking skills of elementary school students. This research is experimental research with quasi-experiment model with Nonequivalent Control Group Design method. The sampling technique is purposive sampling with 50 research samples. The instrument technique uses essay questions as many as 10 numbers of questions using the ELIPSS rubric for critical thinking skills. Data were analyzed descriptively and inferentially. The results of the study found that there was a significant effect of CFGC learning model on the critical thinking ability of science elementary school students. The results of this study can be used as a basis for education to adopt a more flexible and technology-based learning model to improve students' critical thinking skills. This learning model can be used with various technological media as a suggestion for future research.